Long-term survival of patients with mantle cell lymphoma after autologous haematopoietic stem-cell transplantation in first remission: a post-hoc analysis of an open-label, multicentre, randomised, phase 3 trial. Issue 9 (September 2021) - Zoellner, Anna-Katharina; Unterhalt, Michael; Stilgenbauer, Stephan; Hübel, Kai; Thieblemont, Catherine; Metzner, Bernd; Topp, Max; Truemper, Lorenz; Schmidt, Christian; Bouabdallah, Kamal; Krauter, Jürgen; Lenz, Georg; et al.
Summary: Background: Autologous haematopoietic stem-cell transplantation (HSCT) in first remission is the current standard treatment in fit patients with mantle cell lymphoma. In this long-term follow-up study, we aimed to evaluate the efficacy of autologous HSCT versus interferon alfa maintenance after chemotherapy without or with rituximab in patients with primary advanced-stage mantle cell lymphoma. Methods: We did a post-hoc, long-term analysis of an open-label, multicentre, randomised, phase 3 trial done in 121 participating hospitals or practices across six European countries. Patients who were aged 18–65 years with previously untreated stage III–IV mantle cell lymphoma and an ECOG performance score of 0–2 were eligible for participation. Patients were randomly assigned (1:1) to receive either myeloablative radiochemotherapy (fractionated total body irradiation with 12 Gy/day 6–4 days before autologous HSCT and cyclophosphamide 60 mg/kg per day intravenously 3–2 days before autologous HSCT) followed by autologous HSCT (the autologous HSCT group) or interferon alfa maintenance (the interferon alfa maintenance group; 6 × 10 6 IU three times a week subcutaneously until progression) after completion of CHOP-like induction therapy (cyclophosphamide 750 mg/m 2 intravenously on day 1, doxorubicin 50 mg/m 2 intravenously on day 1, vincristine 1·4 mg/m 2 [maximum 2 mg] intravenously on day 1, and prednisone 100 mg/m 2 orally on days 1–5; repeated every 21 days for up to 6 cycles) without or with rituximab (375 mg/m 2 intravenously on day 0 or 1 of each cycle; R-CHOP). The primary outcome was progression-free survival from end of induction until progression or death among patients who had a remission and the secondary outcome was overall survival from the end of induction until death from any cause. We did comparisons of progression-free survival and overall survival according to the intention-to-treat principle between both groups among responding patients and explored efficacy in subgroups according to induction treatment without or with rituximab. Hazard ratios (HRs) were adjusted for the mantle cell lymphoma international prognostic index (MIPI) numerical score, and in the total group also for rituximab use (adjusted HR [aHR]). This trial was started before preregistration was implemented and is therefore not registered, recruitment is closed, and this is the final evaluation. Findings: Between Sept 30, 1996, and July 1, 2004, 269 patients were randomly assigned to receive either autologous HSCT or interferon alfa maintenance therapy. The median follow-up was 14 years (IQR 10–16), with the intention-to-treat population consisting of 174 patients (93 [53%] in the autologous HSCT group and 81 [47%] in the interferon alfa maintenance group) who responded to induction therapy. The median age was 55 years (IQR 47–60), and R-CHOP was used in 68 (39%) of 174 patients. The median progression-free survival was 3·3 years (95% CI 2·5–4·3) in the autologous HSCT group versus 1·5 years (1·2–2·0) in the interferon alfa maintenance group (log-rank p<0·0001; aHR 0·50 [95% CI 0·36–0·69]). The median overall survival was 7·5 years (95% CI 5·7–12·0) in the autologous HSCT group versus 4·8 years (4·0–6·6) in the interferon alfa maintenance group (log-rank p=0·019; aHR 0·66 [95% CI 0·46–0·95]). For patients treated without rituximab, the progression-free survival adjusted HR for autologous HSCT versus interferon alfa was 0·40 (0·26–0·61), in comparison to 0·72 (0·42–1·24) for patients treated with rituximab. For overall survival, the adjusted hazard ratio for HSCT versus interferon alfa was 0·52 (0·33–0·82) without rituximab and 1·05 (0·55–1·99) for patients who received rituximab. Interpretation: Our results confirm the long-term efficacy of autologous HSCT to treat mantle cell lymphoma established in the pre-rituximab era. The suggested reduced efficacy after immunochemotherapy supports the need for its re-evaluation now that antibody maintenance, high-dose cytarabine, and targeted treatments have changed the standard of care for patients with mantle cell lymphoma. Funding: Deutsche Krebshilfe, the European Community, and the Bundesministerium für Bildung und Forschung, Kompetenznetz Maligne Lymphome.